1998
DOI: 10.1002/(sici)1520-6793(199812)15:8<735::aid-mar2>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between waiting in a service queue and evaluations of service quality: A field theory perspective

Abstract: Both empirical evidence and logic suggest that there is a strong negative correlation between waiting time and a customer's evaluation of the quality of a service. The evaluation of service, in turn, is related strongly to customers' loyalty and other important outcomes. A conceptual model, based on field theory, is developed. The model integrates key variables derived from recent studies of consumer waiting behavior. Also incorporated are relevant constructs from the extant services literature, including the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
132
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(142 citation statements)
references
References 22 publications
7
132
0
3
Order By: Relevance
“…In situations where the actual waiting period cannot be changed, it is critically important for financial service providers to formulate strategies to manage customer PWT in terms of filled time (Taylor, 1994(Taylor, , 1995Hui et al, 1997), service stage (Houston et al, 1998), uncertain waits (Taylor, 1994;Kumar and Krishnamurthy, 2008), unexplained waits (Hui and Tse, 1996), and fairness (Oberholzer-Gee, 2006;Voorhees et al, 2009). An organisation's waiting management (WTM) strategies are a set of waiting time fillers meant to reduce the consumer's PWT dissatisfaction.…”
Section: Waiting Time Management (Wtm) Strategies and Waiting Time Samentioning
confidence: 99%
“…In situations where the actual waiting period cannot be changed, it is critically important for financial service providers to formulate strategies to manage customer PWT in terms of filled time (Taylor, 1994(Taylor, , 1995Hui et al, 1997), service stage (Houston et al, 1998), uncertain waits (Taylor, 1994;Kumar and Krishnamurthy, 2008), unexplained waits (Hui and Tse, 1996), and fairness (Oberholzer-Gee, 2006;Voorhees et al, 2009). An organisation's waiting management (WTM) strategies are a set of waiting time fillers meant to reduce the consumer's PWT dissatisfaction.…”
Section: Waiting Time Management (Wtm) Strategies and Waiting Time Samentioning
confidence: 99%
“…The phenomena of delay has been a popular research subject in queueing theory, see [12]. The interest in delay prediction is motivated by psychological insights on the negative effect of waiting on customer satisfaction [13]. Field studies have found that seeing the line ahead moving and getting initial information on the expected delay, both have a positive effect on the waiting experience [14,15].…”
Section: Background and Problem Specificationmentioning
confidence: 99%
“…Waiting negatively affects service quality evaluation (Antonides et al 2002;Houston et al 1998;Cho and Kim 2007) and reduces customer satisfaction with service (Davis and Vollmann 1990;Davis and Heineke 1998;Leclerc et al 1995). Furthermore, waiting induces negative emotions such as anger and uncertainty (Taylor 1994), which consequently mediate the relationship between service quality evaluation and customer satisfaction (Hui and Tse 1996;Houston et al 1998). …”
Section: Positive and Negative Customer Responses To Waitingmentioning
confidence: 99%
“…Research on industries such as medical services (Tansik and Routhieaux 1999;Yoon and Kim 2003), bank services (Chebat et al 1995;Houston et al 1998;Katz et al 1991), dining services (Davis and Heineke 1998;Davis and Vollmann 1990), and airline services (Taylor 1995) focused on how to reduce the negative impact of long waits.…”
Section: Introductionmentioning
confidence: 99%